DESIGN OF LABORATORY SCALE REAL-TIME MONITORING SYSTEM FOR UNDERGROUND MINING USING WIRELESS NETWORK (Cyberspace: Jurnal Pendidikan Teknologi Informasi, 2022)
Underground mining is one of the mining systems that has a high potential risk of work accidents. One of the potential dangers is the emergence of gasses that can cause disruption of the respiratory system in humans. To minimize this risk, it is necessary to periodically monitor the gas that appears in the work area. This study aims to design a laboratory environmental monitoring system for underground mining using Arduino Uno as a controller that uses sensors of temperature, oxygen, carbon dioxide, and wind speed. Sensor data is sent wirelessly to the main monitoring system with point to point topology. The design of the software is carried out as a place to store data from the sensor which is then displayed in a monitoring information system in real time. From the results of system testing, sensor data is taken in a span of 1 second which is generated by a system with an accuracy rate of 99.9%. Overall, the system can be used properly to real monitor the environmental quality of underground mines.
Keywords: Monitoring System; Underground Mining; Wireless Network